Biomechanical and Ergonomic Evaluation of Joint Position in Assistive Chopsticks During a Food-Pulling Task - Kodai Kitagawa; Yuzuki Kudo; Tadateru Kurosawa (KHD Production, 2026)
Assistive chopsticks equipped with joint mechanisms effectively support individuals with limited hand function by facilitating grasping and food serving. However, their biomechanical impact on food-pulling, a fundamental preparatory eating action requiring sustained force and control, remains unclear. This study investigated the effects of joint position in assistive chopsticks on food-pulling performance and physical load. Ten healthy young males performed a standardized food-pulling task using their non-dominant hand to simulate reduced manual dexterity. Participants evaluated three chopstick conditions: conventional (unjointed), handle-joint, and top-joint. During the task, a simulated food item was pulled toward the participant while maximum pulling force, flexor digitorum superficialis muscle activity (via surface electromyography), and subjective comfort (via a visual analog scale) were quantitatively measured. Statistical analysis revealed no significant differences among the three conditions for maximum food-pulling force, normalized muscle activity, or subjective comfort. These findings indicate that variations in joint position do not adversely affect food-pulling performance or increase neuromuscular load. Although the participant sample was restricted to healthy young males, this study provides critical preliminary evidence that assistive chopsticks can be structurally optimized for specific grasping or serving tasks without compromising fundamental food manipulation. Ultimately, these results offer valuable design flexibility for the future development of ergonomic, task-specific assistive eating devices.